1994
DOI: 10.1007/bf00014669
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of selectable and non-selectable transgenes in maize after introduction by particle bombardment

Abstract: Zea mays transformants produced by particle bombardment of embryogenic suspension culture cells of the genotype A188 x B73 and selected on kanamycin or bialaphos were characterized with respect to transgene integration, expression, and inheritance. Selection on bialaphos, mediated by the bar or pat genes, was more efficient than selection on kanamycin, mediated by the nptII gene. Most transformants contained multicopy, single locus, transgene insertion events. A transgene expression cassette was more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(93 citation statements)
references
References 36 publications
6
87
0
Order By: Relevance
“…FISH screening of root tips of regenerated seedlings by using pWY96 (7) and pAHC25 probes separately revealed that both transgenes were present at the same locations in 84% of the transformants, as is often the case with cobombardment (14). There were 53 targeted B or miniB chromosomes that had both the pWY96 and pAHC25 transgenes (SI Table 2).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…FISH screening of root tips of regenerated seedlings by using pWY96 (7) and pAHC25 probes separately revealed that both transgenes were present at the same locations in 84% of the transformants, as is often the case with cobombardment (14). There were 53 targeted B or miniB chromosomes that had both the pWY96 and pAHC25 transgenes (SI Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…In the progeny of 76-10, only 2 of 12 individuals with the transgene showed GUS expression. This transgene might have undergone rearrangement or gene silencing, which occurs frequently in transformants recovered from biolistic-mediated gene transformation (14). In contrast, all individuals without a detectable transgene were negative for the GUS assay.…”
Section: Resultsmentioning
confidence: 99%
“…Although instability of transgene expression has been observed in maize (Klein et al, 1990) and rice (Register et al, 1994;Cooley et al, 1995), few published reports of gene silencing in transgenic monocots exist. Although an association between the presence of multiple copies of introduced gene sequences and lack of expression has been reported for maize (Register et al, 1994) and rice (Rathore et al, 1993;Cooley et al, 1995), no insight into the mechanism of silencing was obtained, other than the observation that low levels of GUS expression in stably transformed maize calli were correlated with methylation of the coding region (Klein et al, 1990).…”
Section: Transgene Silencing and Methylationmentioning
confidence: 99%
“…Although an association between the presence of multiple copies of introduced gene sequences and lack of expression has been reported for maize (Register et al, 1994) and rice (Rathore et al, 1993;Cooley et al, 1995), no insight into the mechanism of silencing was obtained, other than the observation that low levels of GUS expression in stably transformed maize calli were correlated with methylation of the coding region (Klein et al, 1990). Similarly, in a recent study a large number of transgenic rice plants produced by biolistics were analyzed and revealed both non-Mendelian inheritance of hygromycin resistance and suppression of GUS expression (Qu et al, 1996), although the molecular basis was not investigated.…”
Section: Transgene Silencing and Methylationmentioning
confidence: 99%
“…A number of plant transformation experiments have reported plants with a mixture of non-Mendelian and Mendelian inheritance of the transgene (Christou et al 1989;Tomes et al 1990;Spencer et al 1992;Walters et al 1992;Hiei et al 1994;Register et al 1994;Peng et al 1995). In our experiments, none of the four events we studied exhibited efficient pollen transmission.…”
Section: Discussionmentioning
confidence: 67%